Aplikasi Dashboard Monitoring Pelaporan Penelitian Pengabdian Masyarakat Dosen Dan Mahasiswa Universitas Bina Insan Lubuklinggau - Bunga Intan; Fido Rizki (LPPM Sekolah Tinggi Teknologi Pagar Alam, 2020)
On the system currently running at LPPM, Bina Insan University, monitoring and evaluation of research result and community service activities that have been carried out by lecturers and students is done manually, Lecturer submits the output of research and community service results that are printed to the LPPM section, then the data input into Microsoft Excel for further processing. From the manual process, it will cause problems and the loss of data or files in printed form. Based on the problems faced by LPPM Division of Bina Insan University in the process of monitoring and evaluating the research results and community service activities by lecturers and students, the LPPM division needs to develop a dashboard application for monitoring and reporting research and community service for lecturers and students. The development of this application applies the waterfall method which consists of several stages, namely analysis, system design, coding and system testing. The system is designed using the Unified Model Language (UML) in which the system is developed with object-based concepts and the programming language used is PHP and MySQL database. From the development of this application it can save time and minimize the occurrence of errors and can assist LPPM in recording, evaluating and reporting on the performance of research and community service for Bina Insan University lecturers and students quickly, precisely and accurately.